Biofuel usage in diesel engines powered by butanol and its blends: A review - Celebi, Yahya; Cengiz, Mazlum; Aydin, Huseyin (Elsevier Sci Ltd, 2025)
Given the progressive nature of science, it is essential to present the most current knowledge. Butanol emerges as a green alternative fuel for internal combustion engines. It has many outstanding properties such as higher energy density, flash point, better engine compatibility, lower volatility, vapor pressure, corrosiveness, explosiveness and hygroscopicity compared to light alcohols. In addition, butanol can be produced from both petroleum and biomass feedstocks. Biomass resources are the key benefit for industrial-scale production and global use. The main goal of this review is to reveal the potential of butanol as an alternative fuel in the transport sector. Accordingly, a significant number of literatures from indexed journals have been cited to display the technical effects of butanol-blended fuels on engine performance, combustion and emission characteristics. The blend variations are divided into four sections: butanol/biodiesel, butanol/diesel, butanol/biodiesel/diesel and butanol/other fuels. Apart from that, the review summarizes the feedstock options, methods for producing butanol, market dynamics, and environmental and human health considerations of butanol. The research highlights that small additions of butanol to biodiesel-diesel blends can enhance brake thermal efficiency and reduce nitrogen oxides emissions, although it may increase brake specific fuel consumption. However, the addition of butanol generally increases hydrocarbon emissions while reducing smoke opacity. The study also notes that butanol blends can lower carbon monoxide emissions compared to petrodiesel, although the impact on emissions varies with blend ratios and engine conditions. This paper aims to serve as a valuable resource for engineers and researchers focused on butanol.
Keywords: Butanol; Diesel engines; Performance; Combustion; Emission; Production